2004
DOI: 10.1002/art.20478
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the gene encoding CD59a in mice increases disease severity in a murine model of rheumatoid arthritis

Abstract: Objective. To investigate the roles of CD59a in the protection of joint tissue in the context of murine antigen-induced arthritis (AIA).Methods. AIA was triggered in CD59a-deficient (CD59a ؊/؊ ) mice and in CD59a-sufficient (CD59a ؉/؉ ) controls; the course and severity of disease were compared between groups. The effects on arthritis of restoring CD59 to the joint in CD59a ؊/؊ mice by use of a membrane-targeted recombinant CD59 were also explored.Results. Disease, as assessed clinically by measurement of join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 36 publications
2
45
0
2
Order By: Relevance
“…For example, opsonization with C3b is the main mechanism by which complement contributes to phagocytosis of pathogenic microorganisms. The hypothesis that C5a and/or MAC are main contributors to the disease is further supported by beneficial effects of oral C5aR antagonist in treatment of arthritis in rat (38) as well as increased arthritis severity in mice lacking the MAC inhibitor, CD59 (39). Interestingly, in the PAI experiment, the level of complement activity was up-regulated at day 70, which is consistent with the fact that several complement factors are acute phase proteins up-regulated upon inflammation.…”
Section: Figuresupporting
confidence: 67%
“…For example, opsonization with C3b is the main mechanism by which complement contributes to phagocytosis of pathogenic microorganisms. The hypothesis that C5a and/or MAC are main contributors to the disease is further supported by beneficial effects of oral C5aR antagonist in treatment of arthritis in rat (38) as well as increased arthritis severity in mice lacking the MAC inhibitor, CD59 (39). Interestingly, in the PAI experiment, the level of complement activity was up-regulated at day 70, which is consistent with the fact that several complement factors are acute phase proteins up-regulated upon inflammation.…”
Section: Figuresupporting
confidence: 67%
“…The complement system contributes significantly to the pathogenesis of RA and other autoimmune diseases [11,12]. Under normal physiological conditions, tissues in the body are protected from complement-mediated damage by expression of multiple complement regulatory proteins that co-operate to inhibit complement activation on selftissues [13].…”
Section: Discussionmentioning
confidence: 99%
“…In the patients' synovial fluid, decreased levels of native complement components and increased levels of activation products have been detected [11]. Furthermore, deposition of activated complement components has been demonstrated in synovial tissue [12]. Various studies on animal models of autoimmune diseases have demonstrated that membrane-bound complement regulatory proteins may critically determine the sensitivity of the host tissues to complement injury in autoimmune and inflammatory disorders [3].…”
Section: Discussionmentioning
confidence: 99%
“…*, p Ͻ 0.05; **, p Ͻ 0.01; ***, p Ͻ 0.001. ns, not significant. been shown to contribute to the pathology of the disease in mice models, as CD59a Ϫ/Ϫ mice develop a more severe arthritis than their wild type counterparts in an antigen-induced arthritis model (23). Furthermore, a membrane-targeted rat CD59 derivative (sCD59-APT542) was shown to decrease disease severity in the same arthritis model in rats (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…been shown to contribute to the pathology of the disease in mice models, as CD59a Ϫ/Ϫ mice develop a more severe arthritis than their wild type counterparts in an antigen-induced arthritis model (23). Furthermore, a membrane-targeted rat CD59 derivative (sCD59-APT542) was shown to decrease disease severity in the same arthritis model in rats (23,24). Increasing our knowledge on mechanisms of complement regulation within the joints is essential for future development of specific complement inhibitors or inhibitors of the factors causing local complement activation suitable for human use with minimal systemic effects.…”
Section: Discussionmentioning
confidence: 99%